Manajemen Kinerja Model Deming dalam Strategi Dakwah Bil Hal pada Panti Asuhan Yayasan Al-Jihad Surabaya - Zulkarnain, Bagus Abdillah; Baharudin, Muhammad Yusuf Saaih; Nurdin, Ali; Hanifah, Najmy; Abdah, Mohammad Nabil Haikal Bin (Idarotuna, 2024)
Da'wah bil-hal or da'wah by action, effectively conveys Islamic values, especially in the orphanage environment. Al-Jihad Foundation Surabaya implements bil-hal da'wah through educational programs, skills, and social activities to shape the morals and independence of foster children. However, the success of this da'wah requires systematic and sustainable management. This research aims to analyze the application of the Deming Model or PDCA Cycle (Plan-Do-Check-Action) in the da'wah strategy at the Al-Jihad Foundation. This research uses a qualitative approach and semi-structured interviews with administrators, Focus Group Discussion (FGD), observation, and literature study. This research used Thematic analysis to identify patterns in PDCA implementation. The research results show that PDCA helps foundations plan structured, consistent, periodic, and sustainable activities. The implementation of PDCA is proven to support the goals of da'wah bil hal, creating an environment conducive to developing children's morals and independence. Thus, PDCA effectively strengthens efforts to achieve da'wah goals systematically and optimally.